2009
DOI: 10.1002/elsc.200800046
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor engineering of Lactobacillus brevis alcohol dehydrogenase by computational design

Abstract: The R‐specific alcohol dehydrogenase from Lactobacillus brevis (Lb‐ADH) catalyzes the enantioselective reduction of prochiral ketones to the corresponding secondary alcohols. It is stable and has broad substrate specificity. These features make this enzyme an attractive candidate for biotechnological applications. A drawback is its preference for NADP(H) as a cofactor, which is more expensive and labile than NAD(H). Structure‐based computational protein engineering was used to predict mutations to alter the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…6). For the measurements in cuvettes the obtained temperature optimum for the LbADH wild-type of about 55°C is in good agreement with reported data [48,49]. However, activity measurements at temperatures above 60°C were not reliable due to fast cofactor deactivation showing half-lives of about 30 min [44].…”
Section: Enzyme Activities Deviate Due To Spatial and Temporal Tempersupporting
confidence: 89%
“…6). For the measurements in cuvettes the obtained temperature optimum for the LbADH wild-type of about 55°C is in good agreement with reported data [48,49]. However, activity measurements at temperatures above 60°C were not reliable due to fast cofactor deactivation showing half-lives of about 30 min [44].…”
Section: Enzyme Activities Deviate Due To Spatial and Temporal Tempersupporting
confidence: 89%
“…A number of reactions were found to be involved in more than one pathway such as reactions catalyzed by alcohol dehydrogenase (ADH) enzymes (EC 1.1.1.1) that can be found in carbohydrate, lipid and amino acid metabolisms in agreement with literature [69]. 37.3% of the total reactions were unique to C. salexigens i OA584 most of which were from amino acid (38 reactions) metabolism followed by carbohydrate metabolism (31 reactions).…”
Section: Resultssupporting
confidence: 73%
“…[5] Overexpression of the transhydrogenase in an engineered E. coli strain might cause ah igherm etabolic load and more energy requirements. [8] The enzyme l-aspartate-b-Scheme1.Three cascade reactionsf or the production of l-homoserine. [7] In addition, somes tudies suggested that NAD(H)-dependent enzymes are preferable in industry,d ue to lower costs and greater stability.…”
Section: Introductionmentioning
confidence: 99%